The seasonal and stage-related cycles of lipid droplets in Sertoli cells in the seasonal breeding mink Mustela vison. - Keeping, Lyndon E. (University of Ottawa (Canada), 1991)
The relationship between Sertoli cell lipid inclusions and spermatogenic activity was investigated using light microscopy and morphometric analysis of the lipid droplet content of Sertoli cells and spermatids from the seasonal breeding mink. Tissue was obtained and analyzed each month during a twelve month period to establish the presence of seasonal and stage-related cycles of lipid droplet content in these cells. It is concluded that the amount of lipid inclusions in Sertoli cells varies with the degree of spermatogenic activity being lowest after the release of mature spermatids in the lumen during the active spermatogenic phase and at the time of maximal testicular regression. Furthermore, cholesterol esters are a component of these lipid inclusions and the seasonal changes in lipid inclusions of Sertoli cells are reflected by seasonal changes in the amount of Sertoli cell cholesterol esters. (Abstract shortened by UMI.)
Keywords: Biology, Cell.